Cultura e transformação: entre casas e coisas no mundo Xavante - Andrade, Marcos Vinicius de Almeida (Universidade Federal de São Carlos, 2019)
In the past decades, public policies in the most diverse areas have been formulated for indigenous peoples. These policies, often engendered by imperatives of national development, are not always congruent with the singularities of these peoples. This paper proposes an anthropological research about the situation found among the Xavante indigenous people, in which the construction of housing promoted by political programs like PNHR and MCMV causes a lot of criticism and questioning by part of the supposed benefited ones, putting in evidence a complex entanglement of relations that are produced from the Xavante modes of inhabiting the enviroment. From an ethnographic case, audiovisual productions and literature review on the Xavante, this research is intended to highlight the multiple relationships established between these people and the myriad of beings who co-inhabit the world, presenting as houses, bodies and things are related to culture and historical transformations, serving to operationalize reflections about themselves and others.
Culture and transformation: houses and things in the Xavante world
Cultura y transformación: entre casas y cosas en el mundo Xavante
Keywords: Xavante; Etnologia; Cultura; Resistencia; Transformacao; Corpo; Casa; Culture; Resistance; Transformation; Body; Houses; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA